2009
DOI: 10.1016/j.mambio.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Tooth wear in captive wild ruminant species differs from that of free-ranging conspecifics

Abstract: The mesowear method evaluates the wear patterns of herbivore cheek teeth by 2 visually evaluating the facet development of the occlusal surfaces. It thus allows 3 classification of most herbivorous ungulates into browsers, grazers or intermediate 4 feeders, due to the fact that in grazers, tooth wear is characterized by a 5 comparatively high degree of abrasion, most probably due to the presence of 6 silicacious phytoliths in grasses, a higher amount of dust and grit adhering to their 7 forage, or both. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 32 publications
0
94
1
2
Order By: Relevance
“…Reduced dental health in some captive mammals has been suggested as one factor limiting lifespan among these taxa in captivity [e.g., Clauss et al, 2007;Jurado et al, 2008;Kaiser et al, 2009]. However, given annual veterinary and dental examinations, tooth cleanings, and a controlled diet, we expected less overall tooth wear and few cases of tooth loss in the Indianapolis Zoo ring-tailed lemur population, when compared with the BMSR sample.…”
Section: Discussion Captive Vs Wild Ring-tailed Lemur Tooth Wearmentioning
confidence: 77%
See 2 more Smart Citations
“…Reduced dental health in some captive mammals has been suggested as one factor limiting lifespan among these taxa in captivity [e.g., Clauss et al, 2007;Jurado et al, 2008;Kaiser et al, 2009]. However, given annual veterinary and dental examinations, tooth cleanings, and a controlled diet, we expected less overall tooth wear and few cases of tooth loss in the Indianapolis Zoo ring-tailed lemur population, when compared with the BMSR sample.…”
Section: Discussion Captive Vs Wild Ring-tailed Lemur Tooth Wearmentioning
confidence: 77%
“…Specifically, we integrated the study of these captive, known-aged lemurs, with controlled diets, annual medical evaluations, dental cleanings, and no predation, to provide a comparative template of patterns of dental wear one might expect in an ''optimal'' population. Although some captive mammals exhibit patterns of tooth wear that exceed those seen in wild populations [e.g., Clauss et al, 2007;Jurado et al, 2008;Kaiser et al, 2009], given their regular medical and dental care, we expected less overall tooth wear and fewer lost teeth in the captive Lemur catta sample when compared with the BMSR population. To our knowledge, ours are the first data comparing dental macrowear between wild and captive similar-aged individuals within a single primate species.…”
Section: Research Questionsmentioning
confidence: 82%
See 1 more Smart Citation
“…Summary statistics (number of specimens n, mean m and standard deviation s.d.) for the dietary estimators (A; microwear coordinate MiC and mesowear score MwS) and the three inter-and intra-community disparities (B, C and D The extinction of European hominoids G. Merceron et al 3107 shown in Kaiser et al (2009). The dental mesowear pattern is scored as follows: 0 for high relief with sharp cusps, 1 for high relief with round cusps, 2 for low relief with sharp cusps, 3 for low relief with round cusps and 4 for low relief with blunt cusps.…”
Section: (B) Methods (I) Mesowear Analysismentioning
confidence: 99%
“…The physical inadequacy of grass hay for a 'moose-type' rumen may lead to bezoars or RR blockage . Additionally, conventional zoo diets, which contain abrasive silicates either in pelleted feeds or in grass-based forages, result in unnatural tooth wear in browsing ruminants (Clauss et al, 2007a;Kaiser et al, 2008). The problem of providing adequate nutrition for 'moose-type' ruminants is finally reflected in their relatively short average life expectancies in captivity (Mü ller et al, 2010).…”
Section: Consequencesmentioning
confidence: 99%